Counseling on Antibiotic Medicines for Business Manager Employees at Kimia Farma Pharmacy Surabaya Business Unit - Dian Parwati; Siti Solihah; Zulfa Noraini; Teguh Setiawan Wibowo (Jurnal Pengabdian Masyarakat Mandira Cendikia, 2024)
Medicines are substances intended for the cure, prevention or relief of disease and its symptoms and other uses in humans and animals. Meanwhile, essential minerals and vitamins can be categorized as drugs because they function to improve the condition due to deficiency of an important substance for the body. There are still many problems related to the use of drugs in the community. Lack of information on how to obtain, use, store and dispose of drugs properly is one of the causes of non-optimal treatment, increased drug side effects, reduced quality of life for patients. DAGUSIBU (Get, Use, Save and Dispose) correctly is a slogan introduced by the Indonesian Pharmacists Association (IAI) in an effort to realize the Drug Aware Family Movement (GKSO). which aims as a step to increase public knowledge about Get, Use, Store and Dispose of drugs properly and correctly. Behavior based on knowledge, awareness and positive attitudes is more stable and lasting. Conversely, if behavior is not based on knowledge and awareness, behavior will quickly disappear and can change again. Counseling was conducted to employees of the business manager, HR division, Procurement, Accounts Receivable and ASMAN PMS, most of whose educational qualifications are not in the health sector. So it is expected to benefit from increased knowledge related to DAGUSIBU